In-hospital outcomes in nonagenarian patients undergoing primary percutaneous coronary intervention. (14th October 2021) - Angelini, F; Franchin, L; Bocchino, P P; De Filippo, O; Morici, N; Wanha, W; Savonitto, S; Trabattoni, D; Cerrato, E; Barbieri, L; De Luca, L; Fortuni, F; et al.
Abstract: Objective: The aim of the present analysis was to evaluate the incidence and predictors of in-hospital adverse outcomes in nonagenarian patients undergoing primary percutaneous coronary intervention (pPCI) for ST-segment elevation myocardial infarction (STEMI). Methods: Consecutive nonagenarian patients undergoing pPCI for STEMI from 2009 to 2019 were retrospectively included in an international multicenter registry. In-hospital all-cause death was the primary outcome. Results: A total of 308 patients were included (mean age 92.5±2.5 years, 65.6% female). Mean systolic blood pressure (SBP) at hospital admission was 130.7±33.5 mmHg, 46 (17%) patients presented with a Killip class III-IV, mean left ventricle ejection fraction (LVEF) was 40.0±11.5% and 147 (58%) patients were independent in everyday activities. In-hospital death occurred in 99 patients (32%). [Figure 1] After multivariate adjustment, lower LVEF (OR per unit reduction 1.08, 95% CI 1.03–1.11, p-value <0.001), lower SBP (OR 0.98 per mmHg reduction, 95% CI 1.01–1.03, p-value 0.001) and being not independent at home (OR 2.56, 95% CI 1.25–5.26, p-value 0.01) resulted independent predictors of in-hospital mortality. [Figure 2] A sensitivity analysis performed in final TIMI 3 flow population confirmed the prognostic role of LVEF and independency on in-hospital mortality. Conclusion: Nonagenarian patients presenting with STEMI and undergoing pPCI have high in-hospital mortality. Independency in everyday life is a strong independent predictor of survival to hospital discharge. FUNDunding Acknowledgement: Type of funding sources: None.